The level of social adjustment of students to the school environment in preventing brawls - Desi Puspita Sari; Syahniar Syahniar; Yeni Karneli (International Journal of Applied Counseling and Social Sciences, 2020)
One of the tasks of development in adolescents is social adjustment to the environment which is the school environment. Frequently, adolescents have problems in making social adjustments because this is one of the difficult tasks of adolescent development. If this condition is left, the teen will experience problems. Based on the existing phenomena, there are still students who have not been able to make social adjustments to the school environment so that such things can make students do deviant behavior like brawls. Fighting itself is a fight between groups. The population in this research was the student of SMK Negeri Padang which 140 students were chosen as the sample of the research. The sampling technique used was a purposive random sampling, and the data collection tools used the Social Adjustment Scale (SPS). The data were analyzed by using descriptive statistical methods with data processing using SPSS version 22. The results revealed that social adjustments in brawl prevention were classified as low (50.7%). Then, in the average, there was 38.6%, and in the high category, there was 10.7 %. Based on the results obtained, a follow-up can be carried out by making a guide to improve students' social adjustment to the school environment in preventing brawl.